DIGITAL MEDIA BASED STAD +3R AS AN INNOVATIVE METHODS FOR WRITING EXPLANATION TEXT TEACHING LEARNING - Yudi Cahyadi; Muhamad Ali Mansyur; Hikmah Hasanah (JLER (Journal of Language Education Research), 2020)
Innovation in learning has to be done,  including IKIP Siliwangi students, learning innovation becomes the background in this research, the innovation in question is to develop existing learning models tailored to the needs of students and combine learning model with digital media. The purpose of find out the results of students' learning in writing expplanation text using innovative methods, and to know the implementation of STAD+ 3R methods based on digital media as innovative methods. The research used is quantitative descriptive in the form of Nonequivalent control groups. The population in this study was 300 grade VIII students. The sampling used purposive sampling and obtained grade VIII B as an experimental class of 30 students and grade VIII A as a control class of 30 students. The results showed the study increased the average score by 21.87 points from 56.13 to 78. Significant differences through statistical test with signification score of 2-tailed independent t test sample test is 0.003 < 0.05, it can be concluded there is a meaningful difference between the control and the experiment class, Implementation of STAD +3R method based on digital media goes very well with the results of students' work in the experiment class with digital products in the form of vlog, pptx and e-book.